Effects of the presence of dogs in the working environment on Slovenian civil servants - Kozjek, Tatjana (Dynamic relationships management journal, 2025)
Dogs in the work environment influence various aspects of work, including lower stress levels, greater motivation, higher job satisfaction and general well-being. This study examined the presence and potential positive effects of dogs in public sector organisations in Slovenia and recommendations for the integration of dogs in such environments. The research was based on a survey and questionnaire based on previous studies. It examined the effects of dogs in the work environment on employees, demographic and organisational differences and barriers to integration. The data was analysed using descriptive statistics, the Shapiro-Wilk test, the Mann-Whitney U test, the Kruskal-Wallis H test, Spearman correlation and ordinal linear regression to assess how the integration of dogs into the work environment influences the perception of their positive impact. The results showed that in organisations where dogs are already present, the demographic factors of those who bring dogs were not significantly different. However, bringing a dog into the work environment was a statistically significant predictor of perceived positive effects, particularly for reducing stress, improving social interactions and increasing job satisfaction. Women were generally more in favour of a dogfriendly policy as they felt it contributed to a more relaxed atmosphere and greater motivation. Younger respondents were also more in favour, while older workers were more against. Although Slovenian legislation does not explicitly regulate dogs in the work environment, the results emphasise the need for a comprehensive approach that also takes into account the practical aspects of integration. Successful implementation requires the adaptation of existing pract ises and regulations as well as strategies to address the challenges associated with the daily presence of dogs. The paper concludes with recommendations to support organisational change and policy measures that would enable the effective introduction of dogs into the public sector work environment.
Keywords: civil servants; delovno okolje; dog; integracija; integration; javni uslužbenci; pes; positive impact; pozitiven vpliv; work environment